Knowledge and Information Management: Effective System for Organizational Growth (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Knowledge Management is necessary in organizations to enhance competitive advantage and decision making. Through Knowledge Management, we can share, develop and apply this knowledge for organizational growth. The purpose of paper is to elicit knowledge from the information collected from faculty and students of learning institutions, academies so that in-house training on skills required for training purpose can be planned. The objective is to identify the type of skill required by potential candidates based on IT industry need, resources in terms of skilled trainer available to train students. Another aspect is to identify the gap of skill required, skill available for training and to identify, plan the area where in-house training is required for faculty members.